Use of cardiac troponins as strong markers for patients with acute coronary syndrome - Virun Vichaibun (Journal of Current Science and Technology, 2014)
Acute myocardial infarction (AMI) is the most important cause of cardiomyocyte necrosis. Cardiac troponin (cTn) T and I are structural proteins unique to the heart and have been used as the preferred cardiac biomarkers in the universal definition of myocardial infarction. Cardiac troponins have demonstrated nearly absolute myocardial tissue specificity and high clinical sensitivity for myocardial ischemia. The recent development of high-sensitivity cardiac troponin (hs-cTn) assays allows detection of very low levels of cTn. The hs-cTn assays have improved the diagnostic accuracy and rapid detection of myocardial infarction. Undetectable hs-cTn rules out AMI with a negative predictive value > 99% on emergency department admission. The diagnosis of acute myocardial damage requires a significant change with serial hs-cTn testing. Current consensus for rapid rule-in proposed a 20% increase within 3 to 6 hours when baseline cTn levels are elevated. In addition, relative increases > 50% above the 99th percentile upper reference limit are found to be the diagnosis of AMI, in the case of negative baseline value. Besides relative change, the absolute values of hs-cTn at emergency department presentation in patients with suspected AMI should be considered as important criteria in the differential diagnosis of the cause of cardiomyocyte damage. Cardiac troponins provide both diagnostic and prognostic information in the setting of acute coronary syndrome (ACS). Elevation of cTn in the absence of ACS should prompt an evaluation for non-thrombotic mechanism of increased cTn levels and direct management at the underlying cause.